Cervical spine findings on MRI in people with neck pain compared with pain‐free controls: A systematic review and meta‐analysis. Issue 6 (5th January 2019) - Farrell, Scott F.; Smith, Ashley D.; Hancock, Mark J.; Webb, Alexandra L.; Sterling, Michele
Abstract : Background: There is uncertainty regarding the clinical significance of findings on MRI in patients with whiplash associated disorder (WAD) or nonspecific neck pain (NSNP). Purpose: To compare the presence of cervical spine MRI findings in people with WAD or NSNP with pain‐free controls. Study Type: Systematic review and meta‐analysis. Population: Adults with WAD ( n = 994), NSNP ( n = 715), or pain‐free controls ( n = 2323). Field Strength: 0.5T, 1.5T, and 3.0T. Assessment: Medline, EMBASE, CINAHL, Web of Science, SCOPUS, and Cochrane CENTRAL databases were searched. Two independent reviewers identified studies for inclusion and extracted data. Risk of bias was assessed using the Quality Assessment Tool for Observational Cohort and Cross‐Sectional Studies. Overall quality of the evidence from meta‐analysis was assessed using the Grades of Recommendation, Assessment, Development, and Evaluation approach. Statistical Tests: Meta‐analysis was performed using a random‐effects model to calculate odds ratios or standard mean differences (SMDs) for binary and continuous data. Results: In total, 31 studies were included (eight comparing acute WAD to controls, 14 comparing chronic WAD to controls, 12 comparing chronic NSNP to controls) comprising 4032 participants. Rectus capitis posterior major cross‐sectional area was smaller in people with chronic NSNP than controls (two studies: SMD –1.18 [95% confidence interval [CI] –1.65, –0.71]). The remaining meta‐analysis comparisons showed no group differences in MRI findings. The quality of evidence was mostly low due to small sample sizes and high heterogeneity. Data Conclusion: Given the typically low‐quality evidence, definitive conclusions cannot be drawn on the presence of MRI findings in individuals with WAD or NSNP compared with pain‐free controls. Level of Evidence : 3 Technical Efficacy : Stage 3 J. Magn. Reson. Imaging 2018.